Field investigation of a dry detention pond with underground detention storage - Mah, Yau Seng; Sai, Hin Lai (IAHS Press, 2012)
A dry pond is an urban drainage component designed to temporarily store stormwater runoff and to encourage infiltration of surface water to the subsurface layer. This paper investigates field measurement of a dry pond at Taiping Health Clinic, Perak, Malaysia that has been functioning well for five years. The pond has a surface area of 195 m2, maximum depth of 32 cm, and a storage capacity of 31.88 m3. The study focused on the infiltration functionality of the constructed dry pond and the results show that it has an average infiltration rate of 125 mm/h and dries up in 330 min after being filled to a depth of 31 mm. A public-domain hydrological model was then employed to simulate hydrographs of ponding and draining, the results of which matched observations with 86–98% accuracy. These results can lead to better understanding of the system and allow duplication of such a drainage design elsewhere.